The 10th Anniversary of the Chemical Weapons Convention’s entering into Force - O. V. Glikman; I. I. Sinyakin (Московский журнал международного права, 2007)
The article is devoted to the Convention on the Prohibition of the Development, Production, Stockpiling and Use of Chemical Weapons and on their Destruction, 13 January 1993 (CWC). In connection with the 10th anniversary of the CWC’s entering into force (29 April 1997) a short review of achieved progress and current problems is of vital importance. Besides the description of today’s status of the CWC and the role the CWC plays in the global process of disarmament and strengthening peace and international security the article contains analysis of several significant issues: prohibition of the use of chemical weapons in war conflicts and international humanitarian law; use of toxic chemicals in law enforcement purposes and the issue of riot control agents, positions of state-parties to the CWC. The article covers different approaches of academicians from The Stockholm International Peace Research Institute (SIPRI), Indiana University School of Law (USA) and officials from The Organization for the Prohibition of Chemical Weapons, Russian Munitions Agency.